CORPORATE GOVERNANCE TERHADAP PERINGKAT SUKUK KORPORASI DI INDONESIA - Endri Endri (University of Merdeka Malang, 2011)
This study aims to estimate the influence of corporate governance mechanisms that are implemented throughinstitutional ownership, independent commissioners, audit committees, managerial ownership, blockholderand the number of ratings of corporate sukuk in Indonesia during the 2007-2009 periods. This study usesmultinomial logistic regression models because there are three categories of sukuk ratings, namely: AA, A, andBBB for 33 sample firms that issued sukuk in the Indonesia. The results of empirical studies have found that theaudit committee and the number of blockholder as an indicator of corporate governance mechanisms affect theranking of corporate sukuk significantly. To be able to increase the ranking of the sukuk is the study recommendsthat the existence of audit committees and the blockholder must be a serious concern for companies thatissue a sukuk in improving the ranking of the sukuk issuance